Response to Hepatitis B virus vaccine in young adults with perinatally acquired HIV infection. Issue 4 (October 2015) - Sadarangani, Manish; Tam, Herman; McDonald, Susan; Fidler, Sarah; Foster, Caroline
Highlights Hepatitis B vaccine is recommended in HIV-positive individuals. Clinic attendance in adolescents and young adults is irregular. Erratic dosing intervals of hepatitis B vaccine did not affect anti-HBs levels. High CD4:CD8, low CD8 and high CD4 nadir were associated with higher anti-HBs.